Pelatihan Fashion Design Digital sebagai Upaya Peningkatan Kompetensi Siswa SMKS Pangeran Antasari Deli Serdang - Joko Bintarto; John John (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
The objective of this training program is to enhance the knowledge and skills of 11th-grade students in the Fashion Design Program at SMKS Pangeran Antasari Deli Serdang in creating digital fashion designs using CorelDRAW. The training aims to improve students’ ability to design fashion digitally, assess the skills they have acquired, and evaluate their satisfaction with the learning process using CorelDRAW software. The training was attended by 36 students from the 11th grade of the Fashion Design Program. The activities were conducted through material presentations, discussions, guided assignments, and program evaluations. Through this training, students gained a better understanding of digital fashion design and improved their ability to create proportionate body sketches and digital fashion illustrations using CorelDRAW software.The results of the training indicate that the objectives were successfully achieved. A total of 90% of participants expressed that they were